The Unseen World, and Other Essays - Fiske, John, 1842-1901 (Salt Lake City, UT : Project Gutenberg, 1998)
"The Unseen World and Other Essays" by John Fiske is a collection of essays written during the late 19th century. The work explores profound philosophical inquiries about existence, the interplay of science and religion, and the nature of the unseen aspects of our universe. Fiske delves into questions regarding human existence and the broader universe, aiming to reconcile scientific understanding with spiritual aspiration. The opening of this work introduces the reader to Fiske$1 (Bs contemplative examination of humanity$1 (Bs place within the universe. He reflects on age-old questions about existence and the unseen world, suggesting that philosophical thought and scientific inquiry have progressed significantly over time. Fiske discusses the evolution of theories regarding the cosmos, the nature of scientific hypotheses, and how they might align with religious belief, illustrating humanity's perennial quest to understand its place in the grand scheme of existence. The opening sets the stage for deeper discussions in subsequent essays, hinting at a harmonious relationship between scientific and spiritual realms. (This is an automatically generated summary.)s
The unseen world -- "The to-morrow of death" -- The Jesus of history -- The Christ of dogma -- A word about miracles -- Draper on science and religion -- Nathan the Wise -- Historical difficulties -- The famine of 1770 in Bengal -- Spain and the Netherlands -- Longfellow's Dante -- Paine's "St. Peter" -- A philosophy of art -- Athenian and American life.
Release date is 1998-10-01
Produced by Charles Keller, and David Widger
Keywords: American essays